Exploring Taiwanese EFL Graduate Students Learning Academic Writing - Ming-Hung Hsieh; Hsueh-Hua Chuang (Department of English Language Education, UIN Sunan Ampel Surabaya, 2022)
Much has been done to explore the successful tips for scholarly publication in higher education, and has revealed the challenges facing periphery scholars; few studies, however, discussed the enculturation of learning how to write their theses in English as a Foreign Language (EFL) contexts from graduate students’ standpoints. This study aims to bridge the gaps in the extant literature on academic writing and yield insights into how research space is created by graduate students from the perspective of community of practice (CoP). In particular, this paper addressed what graduate students might encounter in terms of graduate students’ beliefs and attitudes toward academic writing and their multidimensional engagement in the academic community. Four graduate students were involved in the study via homogeneous sampling from four universities in Taiwan. To obtain rich data, semi-structured interviews were adopted, audio-recorded, transcribed, and re-constructed. The results highlighted graduate students’ needs for systematic training of research paper writing. The participants believe that they may benefit more from thorough academic training, whereas they found their academic writing training and writing proficiency insufficient. This study concludes with pedagogical implications for rigorous course design and training for English for Academic Purposes (EAP) writing professionals to improve the quality of EFL academic writing.